2008
DOI: 10.1016/j.jadohealth.2008.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Mental and Physical Health Problems in High-Risk Adolescents: A Longitudinal Study

Abstract: Purpose-This longitudinal study examined the relationship between mental and physical health problems in a sample of high-risk youth served in the public sector.Methods-Participants included youth ages 9 to 18 at baseline, randomly sampled from one of five public service sectors in San Diego County, California and youths may have been active to more than one sector. Diagnoses for mood, anxiety, and disruptive disorders based on structured diagnostic interviews were determined at baseline and data regarding hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 38 publications
1
40
0
Order By: Relevance
“…This finding is consistent with other studies that have found high rates of medical and psychiatric comorbidity among children and adolescents. 9,16,24,25 We found a particularly strong association between irritable bowel syndrome and anxiety, which is not surprising, as anxiety and stress are thought to exacerbate the symptoms of irritable bowel syndrome. 31 Similarly, migraine has been found to be related to a number of psychiatric comorbidities, 32,33 which could represent some shared vulnerability or emotional distress resulting from dealing with the chronic pain of migraine.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…This finding is consistent with other studies that have found high rates of medical and psychiatric comorbidity among children and adolescents. 9,16,24,25 We found a particularly strong association between irritable bowel syndrome and anxiety, which is not surprising, as anxiety and stress are thought to exacerbate the symptoms of irritable bowel syndrome. 31 Similarly, migraine has been found to be related to a number of psychiatric comorbidities, 32,33 which could represent some shared vulnerability or emotional distress resulting from dealing with the chronic pain of migraine.…”
Section: Discussionsupporting
confidence: 54%
“…11 Asthma, diabetes, heart disease, infectious diseases, and digestive disorders have all been found to be associated with an increased prevalence of BHCs at some point in their lives. 11,24 Comorbidity between BHCs and medical conditions can also complicate treatment regimens, 25 increase health care use and costs, 26 and compromise health outcomes, 9,27 which supports the need for a better understanding of the prevalence of these comorbidities.…”
Section: Journal Of the American Academy Of Child And Adolescent Psychimentioning
confidence: 99%
“…Although the negative impact of absenteeism from the classroom on academic achievement can be easily understood, no study has been done to reveal the effect of presenteeism on academic performance. If students' mental and physical illnesses are left untreated in the early stage, these conditions will become aggravated, leading to the need for long-term medical treatment [6]. Recognition of a student's health condition in the early stage might be crucial to decrease the risk of further morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…Adolescents with untreated depression have impaired functioning in all domains, lower academic achievement, more unintended pregnancies, increased incidence of suicide, and are more likely, than adolescents without depression, to use substances like tobacco, alcohol, and illegal drugs (McCarthy, et al, 2008; Kuehn, 2005). Recent evidence links untreated depression during adolescence with the chronic health problems of infectious diseases, respiratory problems, and difficulty maintaining a healthy weight (Schinke, Fange, & Cole, 2008; Aarons, et al, 2008). When depression is unresolved in adolescence, the long-term consequences of depression involve high health care utilization, poor overall health, and increased work impairment related to low physical health in young adulthood (Keenan, Miller, Hammen, & Brennan, 2007).…”
mentioning
confidence: 99%